The effect of intensity of MGMP activities, school climate, and work commitments on the professionalism of economics high school teachers - Pangestika, Ratna Rosita; Setiawan, Risky (Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This study aims to determine the effect of the intensity of MGMP activities, school climate, and teacher work commitment on the professionalism of high school teachers in Economics in the City of Yogyakarta. This research is an ex-post facto research with a quantitative approach. This research is a population study, where the research subjects were all high school economics teachers in Yogyakarta, where the technique of collecting subjects used was saturated sampling. Data were obtained by non-test through questionnaires, interviews, and documentation. Validity testing is done by Expert Judgment and Confirmatory Factor Analysis (CFA). Reliability testing uses Cronbach's Alpha (Î±). Data analysis using multiple regression statistical techniques. The results showed that the intensity of MGMP activities had an effect on teacher professionalism with an R-squared value of 14.2%, school climate had an impact on teacher professionalism with an R-squared value of 28%, and work commitment had an effect on teacher professionalism with an R squared value of 9.3%.